الشبكات التعاونية بين المكتبات : مقومات الإنشاء ورهانات التنفيذ - زيات، ليليا Zayat, Lilia; بودربان، عز الدين (جامعة عبد الحميد مهري - قسنطينة 2, 2017)
Libraries are a part that cannot be dissociated from modern society. They are even one of the means of its development. Their success depends mainly on their degree of internal and external interaction. The wish of libraries for providing information to users in order to respond to their research needs remains the major factor that pushes these institutions to integrate collaborative projects. We have noticed various satisfactory experiences in this field throughout the world, whereas the Arab experiences remain limited and face difficulties. In this matter, we intended to lead a research, on the one hand, on the constituents of collaborative networks which are really the real support of libraries’ development and libraries’ perennity, and, on the other hand, on their establishment in our libraries. We took as an example some model experiences online such as: The Online Computerized Library Center, the Research Library Information Network, and the French National Network for Libraries of Mathematics. We adopted in our research the descriptive approach that seemed to us as suitable for analyzing and explaining. The fundamental result of our study shows that libraries should introduce multiple changes on the administrative, organizational and technical scale in order to set up the pillars for a mutual policy that assures the transfer of information between the collaborative networks’ members.
إن المكتبات جزءا لا يتجزأ من كينونة المجتمع الحديث وإحدى وسائل تطوره، ويعتمد نجاحها بشكل أساسي على مدى تفاعلها مع بيئتها الداخلية والخارجية. إن رغبة المكتبات في توفير المعلومات للمستفيدين لمقابلة احتياجاتهم البحثية، كان ولا يزال الدافع الأساسي تأمين أكبر قدر ممكن من المصادر والمعلومات لجمهور المستفيدين عبر منافذ الشبكة ومكتباتها. ولقد برزت على الساحة الدولية الكثير من التجارب الناجحة في هذا المجال، في الوقت الذي تظل فيه التجارب العربية محدودة تواجه الصعوبات. لذلك فقد ارتأينا البحث في مقومات الشبكات التعاونية فهي الدعم لتطورها واستمرارها، وفي عوامل نجاحها ومعوقاته وفي رهانات تنفيذها في مكتباتنا، معتمدين على بعض التجارب الرائدة في هذا المجال وهي مركز المكتبات المحوسبة على الخط OCLC، شبكة معلومات مكتبات البحث RLIN والشبكة الوطنية الفرنسية لمكتبات الرياضيات RNBM. وقد اعتمدنا في هذه الدراسة على المنهج الوصفي باعتباره الأنسب للتحليل والتفسير. ومن بين أهم ما توصلنا إليه أن على المكتبات أن تسعى لإحداث العديد من التغييرات على المستوى الإداري، التنظيمي والتقني لإرساء دعائم سياسة مشتركة لبث المعلومات بين أعضاء الشبكات التعاونية.
Keywords: الشبكات التعاونية -- المكتبات ومراكز المعلومات -- تكنولوجيا المعلومات